Near-infrared methane sensor based on a distributed feedback laser. Issue 2 (7th February 2019) - Wang, Jianing; Li, Bin; Lin, Guanyu; Ma, Qingjun; Wang, Shurong; Piao, Mingxu
Abstract: In this article, a near-infrared methane detection system using tunable diode laser absorption spectroscopy technology was designed and implemented. The distributed feedback laser was driven by a self-developed temperature and current controller to allow scanning the selected absorption wavelength at 1654 nm. Laser temperature fluctuation was lower than 0.01%, and the output emission wavelength was linear and stable. The emitted beam passed a reflective gas chamber and was received by the Indium Gallium Arsenide photodiode detector. Through a data acquisition card, a digital lock-in amplifier was developed to extract the second harmonics with real-time monitoring and adjustment. Based on Allan deviation analysis, the limit of detection was about 48 ppm with a path length of 30 cm, at an integration time of 6 s. The experimental results revealed a maximum detection error of less than 3% at a gas concentration higher than 100 ppm. The fluctuations rates in long-term (9 hr) stability measurements for 1 × 10 3  ppm and 1 × 10 4  ppm methane samples were 0.8% and 0.48%, respectively, indicating good stability for the sensor. In the control module design, compared with previous reports on methane detection systems, the current system uses a self-developed temperature controller, a current driver and a signal processor, to allow real-time display and adjustments. The potential for adjustable wavelength scanning is available for multi-gas detection based on a single detection system.